Dolphin Prey Availability and Calorific Value in an Estuarine and Coastal Environment - McCluskey, Shannon M.; Bejder, Lars; Loneragan, Neil R. (Frontiers in Marine Science, 2016)
Prey density has long been associated with prey profitability for a predator, but prey quality has seldom been quantified. We assessed the potential prey availability and calorific value for Indo-Pacific bottlenose dolphins (Tursiops aduncus) in an estuarine and coastal environment of temperate south-western Australia. Fish were sampled using three methods across three regions (Estuary, Bay and Ocean) in the study area using a 21.5 m beach seine, multi-mesh gillnet, and fish traps. The total biomass and numbers of all species and those of potential dolphin prey were determined in austral summers and winters between 2007 and 2010. The calorific value of 19 species was determined by bomb calorimetry. The aim of the research was to evaluate the significance of prey availability in explaining the higher abundance of dolphins in the region in summer versus winter across years. A higher abundance of prey was captured in the summer (mean of two summer seasons ± 1 SE = 12,080 ± 160) than in the winter (mean of two winter seasons = 7,358 ± 343) using the same number of gear sets in each season and year. In contrast, a higher biomass of potential dolphin prey, of higher energy content, were captured during winters than summers, when fewer dolphins are present in the area. Variability was significant between season and region for the gillnet (p < 0.01), and seine (p < 0.01). The interaction of season and region was also significant for the calorific content captured by the traps (p < 0.03), and between the seasons for biomass of the trap catch (p < 0.02). The dolphin mother and calf pairs that remain in the Estuary and Bay year round may be sustained by the higher quality, and generally larger, if lesser abundant, prey in the winter months. Furthermore, factors such as predator avoidance and mating opportunities are likely to influence patterns of local dolphin abundance. This study provides insights into the complex dynamics of predator – prey interactions, and highlights the importance for a better understanding of prey abundance, distribution and calorific content in explaining the spatial ecology of large apex predators.